2016
DOI: 10.1097/ccm.0000000000001271
|View full text |Cite
|
Sign up to set email alerts
|

IV Immunoglobulin for Acute Lung Injury and Bacteremia in Pseudomonas aeruginosa Pneumonia*

Abstract: IV immunoglobulin administration had a significantly protective effect against lethal infection from virulent P. aeruginosa. Prophylactic IV immunoglobulin administration at the highest dose was comparable with that achieved by administrating a specific anti-PcrV polyclonal IgG into the mice. The mechanism of protection is likely to involve the synergic action of anti-PcrV titers and antibodies against some surface antigen(s) that block the type III secretion system-associated virulence of P. aeruginosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 60 publications
1
35
0
Order By: Relevance
“…This IgG dose was selected on the basis of the results from our previous animal studies, where we reported on the dose-dependent effect of commercially available intravenous immunoglobulin solution. 26 The survival rates and body temperatures of the mice were monitored for 24 h after infection (Fig. 1A and B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This IgG dose was selected on the basis of the results from our previous animal studies, where we reported on the dose-dependent effect of commercially available intravenous immunoglobulin solution. 26 The survival rates and body temperatures of the mice were monitored for 24 h after infection (Fig. 1A and B).…”
Section: Resultsmentioning
confidence: 99%
“…These results imply that high titer anti-PcrV serum from individuals is protective against virulent P. aeruginosa, predominantly by PcrV blockade, and that the antibody fraction from such high titer sera can target other surface proteins in this bacterium, thereby enhancing its prophylactic potency, as we have reported previously. 26 Therefore, in addition to the inhibition of type III secretion-associated virulence by PcrV blockade, human IgG that contains specificities to other P. aeruginosa surface antigens might have contributed to the biological effects observed in our animal models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies looking at directed antibodies have shown a decrease in airway inflammation and the potential to reduce the prevalence of pneumonia in patients already colonized with P. aeruginosa. In this issue of Critical Care Medicine, Katoh et al (11) examine the utility of IVIG in reducing inflammation, lung injury, and mortality in a mouse model of P. aeruginosa pneumonia. They compared IVIG to a directed antibody and a placebo and showed a reduction in lung injury in their animal model when administered prophylactically.…”
mentioning
confidence: 97%